Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00330-010-1982-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of micro-CT for emphysema assessment in mice: comparison with non-radiological techniques

Abstract: Histomorphometry is the most sensitive technique since it detects airspace enlargement before the other methods (1 h after treatment). Micro-CT correlates well with histology (r2 = 0.63) proving appropriate for longitudinal studies. Functional test parameters do not necessarily correlate with the extent of emphysema, as they can be influenced by acute inflammation. Finally, cytokine measurements correlate with the presence of inflammation in histology but not with emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 25 publications
(35 reference statements)
4
53
1
Order By: Relevance
“…Noninvasive, serial imaging of animal models should ideally result in quantitative datasets that allow for longitudinal assessment, comparisons between different groups, including the effect of therapeutic interventions, and detailed topographic information documenting the extent of disease in individual animals. Micro-CTbased protocols for the quantification of a variety of pulmonary emphysema models in mice have been proposed, and agreement with current gold standard evaluation of histopathology has been reported (2,8,21). We also have recently reported the use of micro-CT to monitor the progression of emphysematous changes in an exacerbation mouse model of COPD by a single administration of elastase followed by lipopolysaccharide (14).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Noninvasive, serial imaging of animal models should ideally result in quantitative datasets that allow for longitudinal assessment, comparisons between different groups, including the effect of therapeutic interventions, and detailed topographic information documenting the extent of disease in individual animals. Micro-CTbased protocols for the quantification of a variety of pulmonary emphysema models in mice have been proposed, and agreement with current gold standard evaluation of histopathology has been reported (2,8,21). We also have recently reported the use of micro-CT to monitor the progression of emphysematous changes in an exacerbation mouse model of COPD by a single administration of elastase followed by lipopolysaccharide (14).…”
mentioning
confidence: 71%
“…Lung parenchyma was arbitrarily defined as a region with X-ray attenuation values between Ϫ1,200 and Ϫ300 HU, and intrapulmonary and surrounding extrapulmonary tissues (e.g., airways, large pulmonary vessels, heart, mediastinal structures, and diaphragm) were excluded. LAA thresholds were arbitrarily established to less than Ϫ700 HU because %LAA of a normal mouse was Ͻ5% referring to a previous publication (2), and it was also set high to make the difference between the groups clearer. The %LAA was calculated using the ratio of the total LAA volume to the end-expiratory lung volume.…”
Section: Methodsmentioning
confidence: 99%
“…24,25 The value of this imaging technique has been studied in disease models of lung fibrosis, lung emphysema and lung neoplasms. [26][27][28][29][30] Nevertheless, this technique has not been used for the assessment of invasive aspergillosis in small animals. Magnetic resonance imaging (MRI) provides images with good spatial resolution and excellent soft tissue contrast, thereby creating the potential to distinguish between different pathological processes occurring within the lung, such as inflammation or necrosis.…”
mentioning
confidence: 99%
“…The mean density of the lungs reported here are similar to those reported by Plathow et al (32) for C57BL/6J female mice of the same age (Ϫ561 HUs) without respiratory gating. Other studies have reported both higher and lower mean densities (2,3,12,24,33,52). The varying values can be explained by the use of the isopressure breath-hold respiratorygating technique for image acquisition, variations in the ages or strains of the animals, or differences in the scaling of images into CT values (10).…”
Section: Discussionmentioning
confidence: 97%